Perbandingan Kemampuan Berpikir Kreatif Menggunakan PBL dan Etnomatematika Ditinjau dari KAM - Ervin Azhar; Zahara Suciani Putri (UNION : Jurnal Ilmiah Pendidikan Matematika, 2022)
This study was conducted to compare the two methods of PBL and Ethnomathematics on students' creative thinking skills, and creative thinking abilities in terms of students' initial mathematical abilities. This study aims to determine which learning methods are superior in creative thinking skills. This study uses a quantitative method with a quasi-experimental type of research. The method of data collection is through the initial mathematical ability test and creative thinking ability test. The research subjects are class VII 8 and VII 9 SMP in Kab. Bekasi for the 2022/2023 academic year. Based on the results of the study, it was found that the average value of students in the ethnomathematics class was better than the PBL class. However, for students with high KAM, the PBL method is more effective, because it is proven that the final score of students is higher in the PBL class. Students with medium and low KAM are better at using the ethnomathematical method for their creative thinking skills.